Does receipt of social housing impact mental health? Results of a quasi-experimental study in the Greater Toronto Area - Dunn, James R.; Smith, Katherine L.W.; Smith, Paula; Moineddin, Rahim; Matheson, Flora I.; Hwang, Stephen W.; Muntaner, Carles; Janus, Magdalena; O'Campo, Patricia (Social science & medicine (1982), 2024)
Affordable housing is commonly described as an important determinant of health, but there are relatively few intervention studies of the effects of housing on health. In this paper, we describe the results of a quasi-experimental, longitudinal study investigating the impacts of receiving social housing among a cohort of 502 people on waitlists for social housing in the Greater Toronto Area, Canada. Specifically, we sought to determine if adults who received housing were more likely than a control group to show improvements in depression, psychological distress, and self-rated mental health 6, 12 and 18 months after moving to housing. Amongst the participants, 137 received social housing and completed at least one follow-up interview; 304 participants did not receive housing and completed at least one follow-up interview and were treated as a control group (47 people provided data to both groups). The difference-in-differences technique was used to estimate the effect of receiving housing by comparing changes in the outcomes over time in the housed (intervention) group and the group that remained on the waitlist for social housing (control group). Adjusted mixed effects linear models showed that receiving housing resulted in significant decreases in psychological distress and self-rated mental health between the groups. Improvements in self-rated mental health between the groups were observed 6, 12 and 18 months after receiving housing (6 months, +2.9, p < 0.05; 12 months, +2.6, p < 0.05; 18 months, +3.0, p < 0.05). Reductions in psychological distress (−1.4, p < 0.05) were observed 12 months after receiving housing. Overall findings suggest that receiving subsidized housing improves mental health over a 6-to-18-month time horizon. This has policy and funding implications suggesting a need to reduce wait times and expand access to subsidized housing. •We present the design for a controlled, quasi-experimental housing study.•Applicants to social housing experience poor health and low socioeconomic position.•Receiving social housing improves mental health over a 6-to-18-month time horizon.•Receiving social housing improves symptoms of psychological distress.